IMPLEMENTASI SISTEM PENGELOLAAN HUTAN BERSAMA MASYARAKAT OLEH LMDH MUSTIKA JATI, DESA GETAS, KECAMATAN KRADENAN, KABUPATEN BLORA, PROVINSI JAWATENGAH - , KENAS WARINGGA DEWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A Joint Forest Management (PHBM) system was an effort to empower society in managing forest aimed to improve company (Perhutani) income, stakeholders and forest village society welfare. A PHBM implementation process related to obstacles both internally and externally. This research was aimed to know an implementation process and dynamics of a Jointly Forest Management in Getas Village Head and also to deliver an alternative recommendation of PHBM system development in Getas Village Head. This research used a quantitative approach by a data gathering technique i.e. interview, observation and a literature study. The analysis was conducted descriptive qualitatively using a qualitative data analysis according to Miles and Huberman and using a SWOT analysis. This research was conducted in Getas Village Head, Kradenan District, Blora Regency, Central Java on May-July 2014 ranging from data collection to the preparation of report. Based on this research result, a PHBM implementation process stage covered socialization, build understanding, identify institution, establish LMDH and communication forum, co-operation agreement planning and also PHBM enforcement, PHBM implementation in Getas Village Head by LMDH Mustika Jati had run 7 years, but it had not shown an optimal result and seemed static, from a SWOT analysis result it identified most affecting internal factor towards PHBM activity in Getas Vilage Head namely a lot of human resources available but their quality was still poor, meanwhile, most affecting external factor was the high of society desire to improve their welfare, however society awareness to exploit field was still labile and their participation in PHBM enforcement was still low. Therefore, it is needed a strategy i.e. approach to society to develop human resources and society awareness.